A model of antecedents of consumers' post brand attitude upon exposure to a cause–brand alliance. Issue 2 (27th September 2012) - Myers, Beth; Kwon, Wi‐Suk
<x xml:space="preserve">Abstract</x> A cause–brand alliance is a type of cause‐related marketing campaign in which the brand supports a cause in response to a consumer purchasing a product associated with the brand. Using the meaning transfer, attribution, and schema theories, the researchers developed a model and hypotheses addressing structural relationships among key antecedents of brand attitude change upon encountering a cause–brand alliance. The model and the hypotheses were tested in the context of hypothetical cause–brand alliance scenarios. Findings indicate cause–brand alliance attitude as a strong direct predictor of post brand attitude, whereas cause involvement, perceived brand motivations, and prior brand attitude indirectly predict post brand attitude through their effects on cause–brand alliance attitude. Cause–brand fit also indirectly predicts cause–brand alliance attitude via perceived brand motivations. Managerial and theoretical implications are discussed. Copyright © 2012 John Wiley & Sons, Ltd.